{3+(-7)} + (-6) add the following integers
Answers
Answered by
2
Step-by-step explanation:
(3+(-7)+(-6)
+ - = -
3-7)+(-6)
-4+(-6)
+ - = -
-4-6= - - = -
=-10
Answered by
1
Answer:
=> -10
Step-by-step explanation:
Given that:-
To Find:- The value of the expression,
By using the method of BODMAS,
It is a method for solving expressions that involves performing numerous arithmetic operations.
As we have,
=>
Simplifying it further, we get
=>
=> -10
Hence, the required solution is -10.
Similar questions